Regulation of Systemic Liquidity Risk - Jin Cao; Gerhard Illing (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2010)
The paper provides a baseline model for regulatory analysis of systemic liquidity shocks. We show that banks may have an incentive to invest excessively in illiquid long term projects. In the prevailing mixed strategy equilibrium the allocation is inferior from the investor's point of view since some banks free-ride on the liquidity provision as a result of limited liability. The paper compares different regulatory mechanisms to cope with the externalities. It is shown that the combination of liquidity regulation ex ante and lender of last resort policy ex post is able to implement the outcome maximizing investor's payoff. In contrast, both “narrow banking” and imposing equity requirements as buffer are inferior mechanisms for coping with systemic liquidity risk.
urn:nbn:de:bvb:19-epub-11306-9
Keywords: E5; G21; G28; 330; Liquidity Regulation; Systemic risk; Lender of last resort; Financial Stability; Bankenliquidität; Bankgeschäft; Kapitaleinkommen; Bankrisiko; Systemrisiko; Bankenaufsicht; Bankenregulierung; Theorie